Preliminary Study on Nano Particle/Photopolymer Hybrid for 3D Inkjet Printing - Yang, Hongyi (2016)
3D inkjet printing is one of the new generation Additive Manufacturing technologies for the production of multi-material and multifunctional 3D products. Due to the critical condition for ink deposition and the stringent requirements for ink solidification, only limited ranges of materials are suitable for 3D inkjet printing. These include low viscosity photo curable polymers, and low melting temperature materials like wax. In this study, a hybrid printing ink prepared by mixing nano silica particles into photopolymer resin was developed for 3D printing, and the influence of silica particle concentrations on the viscosity, surface tension, printability and mechanical properties of cured polymer was studied. Results show that untreated nano silica particles would influence the rheological properties which is critical to the printability, but did not improve the mechanical properties due to the aggregation of nanoparticles during photo curing.